Effect of inflammatory response before mechanical thrombectomy on prognosis in stroke patients - Aytac, Emrah; Balgetir, Ferhat; Genc, Yule Kavak; Gonen, Murat; Dogan, Hasan; Akpinar, Cetin Kursad (Literatura Medica, 2024)
Background and purpose - Mechanical thrombectomy is the most important treatment modality in acute stroke; despite successful thrombectomy, good functional outcome is not achieved in a significant proportion of patients. This study examined the effect of neutrophil lymphocyte ratio (NLR) values at admission on functional outcomes in successfully recanalized patients. Methods - Patients who underwent mechanical thrombectomy due to anterior system major vessel occlusion were retrospectively analyzed and compared with the admission NLR values and 3-month clinical modified Rankin Scale (mRS) scores of successfully recanalized patients. Results - Of a total of 126 patients who underwent thrombectomy within the specified period, 97 patients with successful recanalization were included in the study. The overall successful recanalization rate was calculated as 77%. The mean NLR of patients with mRS <= 2 (n=65) was found to be significantly lower than patients with mRS >= 3 (n=32) (p<0.001). A weak and significant correlation was found between National Institutes of Health Stroke Scale (NIHSS) value and NLR (r= 0.315, p=.002). Conclusion - NLR value has been found to be associated with futile recanalization in mechanical thrombectomy patients. There fore, we think that suppression of inflammation before thrombectomy will increase the chance of successful thrombectomy.
A mechanikus thrombectomia el?tti gyulladásos válasz hatása a stroke-betegek prognózisára
Keywords: tomy; inflammation; neutrophil to lympho; cyte ratio; prognosis